Disclosing Food Vloggers on YouTube: The Effects of Trust on Customer Engagement and Repurchase Intention - Hidayanti, Hidayanti (Journal of Business, Management, and Social Studies, 2021)
The purpose of this study was to substantiate a variety of statements, including the following: To begin, consumer trust influences how customers interact with food vloggers. Second, the customer’s personal connection to food vloggers influences their involvement with food vloggers. Thirdly, client interaction with food vloggers has an effect on repurchase likelihood. Fourth, customer trust has a direct effect on the likelihood of repurchase. This study applies Structural Equation Model (SEM) techniques using Partial Least Squares (PLS) approach. The study took place in Jakarta area for 5 months, from January to May of 2021. The method used for this study mainly retrieved using online questionnaires that consist of survey items represented of the variables used on this study including customer trust, customer engagement, and repurchase intention. Decision-makers should place a greater emphasis on food and beverage influencer marketing, particularly with regard to food vloggers. This is because research indicates that influencer marketing can boost customer trust and engagement, resulting in increased repurchase intentions. Using criteria such as trust and consumer contact with vloggers, this study examines the proclivity of prior customer behavior to predict customers’ chance of repurchase intention (video bloggers).